2022
DOI: 10.3390/medicina59010014
|View full text |Cite
|
Sign up to set email alerts
|

Using a Modified Polysaccharide as a Hemostatic Agent Results in Less Reduction of the Ovarian Reserve after Laparoscopic Surgery of Ovarian Tumors—Prospective Study

Abstract: Background and Objectives: The study investigated whether the method of achieving hemostasis affects the ovarian reserve in patients undergoing laparoscopic surgery due to ovarian tumors or cysts. Materials and Methods: Patients with unilateral tumors or ovarian cysts, who qualified for laparoscopic tumor enucleation, were randomly selected to receive modified polysaccharides or bipolar coagulation. Ovarian reserve was analyzed by anti-Mullerian hormone (AMH) level. Results: The study included 38 patients: 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Bipolar coagulation of the ovarian bleeding site is another effective method of hemostasis but can also potentially harm the surrounding ovarian tissue. Therefore, to avoid damage to healthy ovarian tissue, hemostasis using various topical hemostatic agents has been suggested as a method of choice whenever possible [ 53 , 54 , 55 ]. Several topical hemostatic agents that exert their effect in a variety of ways are currently available in a range of preparations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar coagulation of the ovarian bleeding site is another effective method of hemostasis but can also potentially harm the surrounding ovarian tissue. Therefore, to avoid damage to healthy ovarian tissue, hemostasis using various topical hemostatic agents has been suggested as a method of choice whenever possible [ 53 , 54 , 55 ]. Several topical hemostatic agents that exert their effect in a variety of ways are currently available in a range of preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively recent agents are those based on polysaccharides, albumin, glutaraldehyde, and inorganic agents. Studies have shown that using hemostatic sealants has a positive effect on the ovarian reserve compared to the use of bipolar coagulation and ovarian suturing, as these patients had better levels of anti-Mullerian hormone and antral follicular count postoperatively [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not contain a control group. Moszynski et al ( 2022 ) described the use of potato starch as a haemostatic agent compared to bipolar coagulation in laparoscopic ovarian surgery and showed that the use of modified potato starch might reduce the loss of ovarian reserve due to reduced need of coagulation. Ziegler and De Wilde ( 2022 ) also demonstrated a reduced adhesiogenesis after laparoscopic adhesiolysis using 4DF in a retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%